A universal symphony: coral reef fish calls exhibit consistent acoustic characteristics across different bioregions - Chapuis, Lucille; Lin, Tzu-Hao; Williams, Ben; Lamont, Timothy A. C.; Karkarey, Rucha; Nava-Martínez, Gabriela G.; Naseem, Aya Maryam Rahil; Radford, Andrew N.; Simpson, Stephen D. (Frontiers in Remote Sensing, 2025)
Coral reefs host diverse fish communities, many of which produce sounds. Passive acoustic monitoring (PAM) has become an essential tool for studying these ecosystems, yet the variability in fish calls across regions remains poorly understood. In this study, we analysed 144 h of underwater recordings collected from six coral reef locations around the world, automatically detecting more than 120,000 fish calls. Using Geometric Morphometrics Methods (GMM), Principal Component Analysis (PCA) and Uniform Manifold Approximation and Projection (UMAP), we examined both the three-dimensional shape and spectro-temporal properties of these sounds. The GMM analysis revealed that fish calls showed remarkable acoustic similarity across geographical areas, with the first two principal components explaining 33% of the total variance. Typical fish calls consisted of short (<1 s), low-frequency sounds (∼500 Hz). The UMAP embedding, based on five key acoustic parameters, revealed a largely homogeneous distribution of fish calls across geographical locations. These results suggest that coral reef fish calls exhibit a level of global consistency, potentially reflecting the conserved structure of fish communities across different biogeographic realms. This study emphasises the potential of unknown fish call analyses as a non-invasive tool to explore fish diversity and assemblages, with future work required to extend these findings to other marine ecosystems and integrate automated species identification systems.